2012
DOI: 10.1002/jmri.23676
|View full text |Cite
|
Sign up to set email alerts
|

MR spectroscopic imaging and diffusion‐weighted imaging of prostate cancer with Gleason scores

Abstract: Purpose: To investigate functional changes in prostate cancer patients with three pathologically proven different Gleason scores (GS) (3þ3, 3þ4, and 4þ3) using magnetic resonance spectroscopic imaging (MRSI) and diffusionweighted imaging (DWI). Materials and Methods:In this study MRSI and DWI data were acquired in 41 prostate cancer patients using a 1.5T MRI scanner with a body matrix combined with an endorectal coil. The metabolite ratios of (ChoþCr)/Cit were calculated from the peak integrals of total cholin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…By contrast, with ADC cut-off values of 0.92×10 −3 mm 2 /s in b values of 0, 2000 s/mm 2 , the sensitivity and specificity were 82% and 77%, respectively, suggesting that high b values were better at detecting intermediate or high risk prostate cancer when compared with standard b values. Previous studies have also reported that the ADC can discriminate between low risk cancers (Gleason score ≤6) and intermediate or high risk cancers (Gleason score ≥7) [30], [34], [35]. Therefore, in patients with prostate cancer, the ADC value may serve as a prognostic indicator.…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, with ADC cut-off values of 0.92×10 −3 mm 2 /s in b values of 0, 2000 s/mm 2 , the sensitivity and specificity were 82% and 77%, respectively, suggesting that high b values were better at detecting intermediate or high risk prostate cancer when compared with standard b values. Previous studies have also reported that the ADC can discriminate between low risk cancers (Gleason score ≤6) and intermediate or high risk cancers (Gleason score ≥7) [30], [34], [35]. Therefore, in patients with prostate cancer, the ADC value may serve as a prognostic indicator.…”
Section: Discussionmentioning
confidence: 97%
“…Several papers have been published that compare receiver PAC with the more invasive ERC [16, 35,36]. Particularly, the use of ERC significantly improves spectral line width; however, good performances are obtained using PAC too.…”
Section: Discussionmentioning
confidence: 99%
“…In particular the ratios between their concentrations, i.e. (Cho+Cr)/Cit or Cho/Cit, are the variables of greatest clinical interest because of their correlation with the Gleason score [16]. Although the use of 1 H-MRS to study metabolic changes in brain and liver tumors is well established and supported by the use of recognized research software (jMRUI [17], LCMODEL [18], and Tarquin [19]), the same is not true for PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies using histopathology specimens as reference standards have shown that mpMRI outperforms conventional anatomical imaging alone for the detection of prostate cancer [33][34][35][36]. There is also evidence that unfavorable findings on mpMRI, especially low ADC values, are associated with adverse histological features [37,38]. Currently, almost all MRI reporting schemes are structured and use a 5-point scale to quantify the likelihood that clinically significant prostate cancer is present within a radiological region of interest.…”
Section: Mri In Active Surveillancementioning
confidence: 99%